Early antiretroviral therapy initiation effect on metabolic profile in vertically HIV-1-infected children. (31st August 2021) - Tarancón-Diez, Laura; Rull, Anna; Herrero, Pol; Vazquez-Alejo, Elena; Peraire, Joaquim; Guillén, Sara; Navarro-Gomez, Maria Luisa; Viladés, Consuelo; Muñoz-Fernandez, Mª Ángeles; Vidal, Francesc
Abstract: Background: Early combined antiretroviral treatment (cART) in perinatally acquired HIV-1 children has been associated with a rapid viral suppression, small HIV-1 reservoir size and reduced mortality and morbidity. Immunometabolism has emerged as an important field in HIV-1 infection offering both relevant knowledge regarding immunopathogenesis and potential targets for therapies against HIV-1. Objectives: To characterize the proteomic, lipidomic and metabolomic profile of HIV-1-infected children depending on their age at cART initiation. Patients and methods: Plasma samples from perinatally HIV-1-infected children under suppressive cART who initiated an early cART (first 12 weeks after birth, EARLY, n  =   10) and late cART (12–50 weeks after birth, LATE, n  =   10) were analysed. Comparative plasma proteomics, lipidomics and metabolomics analyses were performed by nanoLC-Orbitrap, UHPLC-qTOF and GC-qTOF, respectively. Results: Seven of the 188 proteins identified exhibited differences comparing EARLY and LATE groups of HIV-1-infected children. Despite no differences in the lipidomic ( n  =   115) and metabolomic ( n  =   81) profiles, strong correlations were found between proteins and lipid levels as well as metabolites, including glucidic components and amino acids, with clinical parameters. The ratio among different proteins showed high discriminatory power of EARLY and LATE groups. Conclusions: Protein signature show a different proinflammatory state associated with a late cART introduction. Its associations with lipid levels and the relationships found between metabolites and clinical parameters may potentially trigger premature non-AIDS events in this HIV-1 population, including atherosclerotic diseases and metabolic disorders. Antiretroviral treatment should be started as soon as possible in perinatally acquired HIV-1-infected children to prevent them from future long-life complications.